Perfil sociodemográfico de doadoras de um banco de leite humano de referência na cidade de São Paulo, Brasil: associação com contaminação por coliformes - Maciel, Ronaldo Franca [UNIFESP] (2019)
Objective: To study the relationship between coliform contamination in human milk from a milk bank and the sociodemographic profile of donor mothers. Methods: Samples of pasteurized human milk (n = 2848) were collected between January 2014 to December 2015 in a public human milk bank. Contamination by total coliforms was evaluated according to the methodology proposed by ANVISA. Sociodemographic data of 233 donor mothers were used in a hierarchical regression model for the definition of significant distal, intermediate and proximal determinants of the "contamination" outcome. Results: A total of 56 out of 233 donors provided at least one sample contaminated with coliforms. The final model showed that the main variable for the risk of contamination by coliforms was to be a donor of a larger number of samples, with an increase of 1% in the prevalence of contamination to each sampled donation unit. By tripling the risk, we observed the following variables: performing milking at home; have fewer than three children and have performed prenatal care on the private network. The following variables doubled the risk of contamination: to have less high school; perform the milk collection with a pump and being a mother of a baby less than 1 month old at the beginning of the donation. The adjusted regression coefficient (R2) of the final model explained 16.4% of the variability of the outcome. Conclusions: Although it is a robust method, the statistical model explained only 16.0% of the variability of the outcome, evidencing that some unknown variables contribute to the contamination of the donated milk. As the collection at home and the use of pumps for extraction are the two main relevant proximal determinants, it’s important to start studies in the households to understand which collection and storage practices are defining the outcome of coliform contamination of donated human milk.